A 150-year Perspective on Swedish Capital Income Taxation - Gunnar Du Rietz; Dan Johansson; Mikael Stenkula (Örebro University School of Business, 2014)
This paper describes the evolution of capital income taxation, including corporate, dividend, interest, capital gains and wealth taxation, in Sweden between 1862 and 2010. To illustrate the evolution, we present annual time-series data on the marginal effective tax rates on capital income (METR) for a marginal investment financed with new share issues, retained earnings or debt. Tax tables covering the period are presented. These data are unique in their consistency, thoroughness and time span covered. The METR is low, is stable and does not exceed five percent until World War I, when it starts to drift somewhat upward and vary depending on the source of finance. The outbreak of World War II starts a period when the magnitude and variation of the METR sharply increases. The METR peaks during the 1970s and 1980s and often exceeds 100 percent. The 1990–1991 tax reform and lower inflation reduce the magnitude and variation of the METR. The METR varies between 15 and 40 percent at the end of the examined period.
Keywords: H21; H31; N44; 330; cost of capital; marginal effective tax rates; marginal tax wedges; tax reforms